The application of Narrative transportation in hard luxury business marketing (online marketing) on the potential customer in the Czech Republic. - Kapusta, Richard (2023)
The luxury industry plays a distinct part of the market and has experienced significant growth and transformation in recent years. The emergence of hard luxury as a separate market segment plays a crucial role in the luxury market. Hard luxury is characterized by high-quality, long-lasting products such as jewelry, watches, and precious accessories. These qualities capture the attention of consumers and marketers have to leverage this interest in order to obtain the best possible results and the desired goal in the market. In this context, understanding the motivation of current and potential customers plays a crucial role. The drivers leading the customers to make a purchase may vary. In terms of justification of the regular purchase of common goods customers tend to rationally justify trier purchase however with luxury goods, especially among hard luxury the motivation seems to be more emotionally based. Therefore the emotional drivers that influence consumer behavior and purchase decisions for hard luxury products are of paramount importance. This bachelor´s thesis dives into these drivers and explains their importance. The main focus is on the Czech and Slovak current and potential hard luxury customers and this thesis has an objective of the correct assigning of these drivers in order to leverage them for the theoretical and practical implications. Once these emotinal drivers are correctly assigned their potential integration will be examined mainly in the brand storytelling to effectively emerge the customer, creating the emotional interest in owning such goods and leveraging these drivers into the hard luxury brands marketing wit the focus on rising online marketing especially trough social media channels. To achieve this main goal, the thesis is divided into several subgoals. First, the thesis comprehensively explains the concept of luxury, luxury industry and the concept of the hard luxury itself.